Impuestos moderados, según Ibn Jaldún - Escartín González, Eduardo (2012)
Ibn Khaldun was an early exponent (XIV century) of the economic liberalism and he had a materialistic conception of history; hence he refers to the institutions in the area of economy and presents his economic thought, which we make it known by employing the methodological absolutism and extracting it directly from his Muqaddimah. We relate some of his ideas with other similar exposed in different periods, and we emphasize those that are still useful today. From his considerations we highlight economic development, currency circulation, wealth, free trade, and price. Ibn Khaldun is taking on higher relevance for the reason that his considerations still seem to describe current situations and his proposals could be implemented today to overcome the economic crisis, even though he did not mention technological innovations that were unthinkable at his time.   Bibliography   ABDÚN, Muhammad Ibn – Sevilla a comienzos del siglo XII. El Tratado de Ibn Abdún; versión de Évariste Lévi-Provençal y Emilio García Gómez. Madrid: Editorial Moneda y Crédito, 1948.XVI, 203 p.; 17 cm. ARISTÓTELES – Metafísica; Madrid: Editorial Gredos, S.A., 1994.582 p.; 21 cm. ISBN 84.249.1666.2 ARISTÓTELES – La Política;4ª ed. Barcelona: Editorial Iberia, S.A., 1967. 306 p.; 19 cm. BIBLE –: Holy Bible Concordance. Red Letter Edition. Cleveland and New York: The World Publishing Company. 746 p., +226 p., +50 p., +124 p.; 14 ilus., 6 xer., 6 map.; 20 cm. BLAUG, Mark – Teoría económica en retrospección; 1ª reimp. Madrid: Fondo de Cultura Económica, 1988. 856 p.; 22 cm. ISBN 84 37502 586. CANTILLON, Richard – Ensayo sobre la naturaleza del comercio en general; 1ª reimp. México: Fondo de Cultura Económica, 1978. 234 p.; 23 cm. ISBN 968.16.0080.0. CERVANTES, Miguel de – El Ingenioso Hidalgo Don Quijote de la Mancha; Madrid: Ediciones Castilla, S.A., 1966. CXI, 2h, 1986 p.; lam., grab.; 19cm. CONSEJO SUPREMO DE CASTILLA: Consulta del Consejo Supremo de Castilla, en Obras del Licenciado Pedro Fernández Navarrete, en Biblioteca de Autores Españoles, Tomo 25, Madrid, M. Rivadeneyra, 1853. XXI, 560 p.; il.; 26 cm. CORÁN–versión de Julio VERNET;2ª ed. Barcelona: Plaza y Janés Editores, S.A., 1984. 588 p.; 18 cm. ISBN 84.01.37054-X. COSTAS COMESAÑA, Antón – “Industrialización y cuestión arancelaria en España. Reflexiones en torno al liberalismo de Laureano Figuerola”, en Economía y economistas españoles, Tomo 4, pp. 459-482; Barcelona: Círculo de Lectores, 2000.767 p.: XL il; 22 cm. ISBN 84.226.7339.8. ESTAPÉ RODRÍGUEZ, Fabián – “Ibn Jaldún: un economista del siglo XIV”, en Economía y Economistas Españoles, Tomo 2, pp. 75-97; Barcelona: Círculo de Lectores, 1999. 667 p.: LXVII, il; 22 cm. ISBN 84.226.7337.1. FERNÁNDEZ NAVARRETE, Pedro – “Conservación de Monarquías”, en Obras de Don Diego de Saavedra Fajardo; y del Licenciado Pedro Fernandez Navarrete; Biblioteca de Autores Españoles, Tomo 25; Madrid: M. Rivadeneyra, 1853. XXI, 560 p.; il.; 26 cm. GARCÍA de CORTÁZAR, José Ángel – La época medieval, Tomo II de Historia de España Alfaguara;4ª ed. Madrid: Alianza Editorial, S.A., 1977. 570 p.; 20 cm. ISBN 84.206.2998.7. GIBB, Hamilton Alexander Rosskeen – “Fiscal Rescript of ‘Umar II”, Arabica II, Leiden, 1955. GODELIER, Maurice: Economía, Fetichismo y Religión en las sociedades primitivas; 2ª ed. Madrid: Siglo XXI de España Editores, S.A., 1978. 4h., 391 p.; 22 cm. ISBN 84.323.0163.9. HARRIS, Marvin – Antropología cultural.1ª ed. Madrid: Alianza Editorial, S.A., 1998. 622 p.; 18 cm. ISBN 84.206.3951.6. JALDÚN, Abú Zayd Abd al-Rahmán ibn–Introducción a la historia universal (Al-Muqaddimah). 1ª ed., 2ª reimp. México: Fondo de Cultura Económica, 1997. 1165 p.; 24 cm. ISBN 968.16.2645.1. JENOFONTE – Económico; versión bilingüe de Juan Gil. Madrid: Sociedad de Estudios y Publicaciones, 1967. 450 p.; 1h,: 24 cm. KEYNES, John Maynard y HENDERSON, Hubert – “¿Puede hacerlo Lloyd George? Examen de la promesa”, en Ensayos de Persuasión. Barcelona: Ediciones Folio, S.A., vol. I, 1997. 2v, 448 p.; 21 cm, ISBN 84.413.0745.8. KEYNES, John Maynard–“Medios para la prosperidad”, en Ensayos de Persuasión. Barcelona: Ediciones Folio, S.A., vol.II, 1997. 2v, 448 p.; 21 cm, ISBN 84.413.0745.8. KEYNES, John Maynard – “Robert Malhus (1766-1835): The First of the Cambridge Economists”, en Essays and Sketches in Biography. New York: Meridian Books, 1956. 347 p,; 18 cm. MARX, Karl Heinrich y ENGELS, Friedrich – La Ideología Alemana.Montevideo: Ediciones Pueblos Unidos, S.A., 1968. 746 p.; 22 cm. MONCADA, Sancho de – Restauración Política de España. Madrid: Instituto de Estudios Fiscales, 1974. 278 p.; 21 cm. MONTESQUIEU, Charles-Louis de Secondat, barón de la Brède y de Montesquieu–Del Espíritu de las Leyes. Madrid: Editorial Tecnos, S.A., 1995. XLVII, 472 p.; ISBN 84.309.1136.7 ORTIZ, Luis – Memorial del contador Luis Ortiz a Felipe II.Edición de José Larraz, Madrid: Instituto de España, 1970. 150 p.; 25 cm. PARDOS MARTÍNEZ, Eva – La incidencia de la protección arancelaria en los mercados españoles. Madrid: Estudios de Historia Económica, nº 37, Banco de España, 1998, 159 p.; 24 cm, ISBN 84.7793.621.8. QUESNAY, François –“Maximes Générales du Gouvernement d’un royaume agricole, et notes sur ces maximes” en Physiocrates/ Quesnay, Dupont de Nemours, Mercier de la Rivière, L’Abbé baudeau. Le Trosne, avec une introduction sur la doctrine des physiocrates, des commentaires et des notices historiques, par M. Eugène Daire.Paris: Librairie de Guillaumin, 1846. 2v, LXXXVIII-424 p.; 429-1027 p.; 25 cm. SMITH, Adam – Investigación sobre la naturaleza y causas de la riqueza de las naciones, 1ª ed, 9ª reimp. México: Fondo de Cultura Económica, 1994. LXXVI, 917 p.; 24 cm. ISBM 968.16.0210.2. VADILLO, José Manuel de – Discursos Económicos-Políticos y Sumario de la España Económica de los siglos XVI y XVII, corregidos y aumentados. Cádiz:Imprenta de D. D. Feros, 1844. 336 p.; 22 cm.